Characterization of bacterial strains isolated from biocide-treated reverse osmosis membrane - Seow, Boon Yee (Nanyang Technological University, 2024)
Many microorganisms inhabit water treatment systems and these microorganisms could accumulate and proliferate on membrane surfaces, even in the presence of biocides and after pre-treatment of membranes. This may adversely impact the performance of a membrane separation process, leading to a shortened membrane life span and increased labour cost for maintenance. Five (5) isolates that are prevalent in the pre-treated Reverse Osmosis membranes were identified and selected to analyse the biofilm formation and growth profile under varying concentrations of 2 types of biocides. The isolates, as single species and mixed-species, were exposed to different concentrations of 2 types of biocides, a chlorine based biocide (IK220) and a isothiazolinone based biocide (EC503) to study their tolerance against the biocides. The results elucidate that different species exhibit varied survival strategies in the presence of biocides. For IK220, Mesorhizobium and Aminobacter demonstrated a propensity to release free-living cells, possibly as a strategy for biofilm dispersion in search of less hostile environments. In contrast, Pedobacter, Acidovorax, and mixed-species biofilms showed tendencies towards metabolic dormancy as a survival mechanism, indicating a significant tolerance to IK220. All species were able to sustain a biofilm lifestyle despite increased biocidal stress, suggesting an important tolerance mechanism for IK220 biocide. For EC503, a stronger biocidal effect was observed. Findings have suggested that Mesorhizobium and Aminobacter were sensitive to EC503 due to a significant decrease in biofilm amount and exhibiting a state of dormancy. Acidovorax was also sensitive to EC503 from 25ppm to 200ppm but developed tolerance at 400ppm due to the increase in cell density to enhance their chances of survival in the toxic environment. Comamonas was also observed to be resistant towards EC503, with an increase in biofilm formed at 400ppm as a defence mechanism against the penetration of the highly concentrated biocide. Similar to IK220, mixed-species biofilms showed tendencies towards metabolic dormancy as a survival mechanism for EC503. Mixed-species was not found to be more tolerant or resistant to the biocide as compared to single-species, which differed from studies, probably due to the competition of nutrients and the complex interspecies interactions that influence the biofilm production that shields it against biocidal stress. As the biofilm amount varied in different species, the extracellular polymeric substance composition was also investigated. Results have shown that extracellular DNA served as a significant component for the structural stability of the biofilm matrix, and extracellular polysaccharides served as a source of nutrient than structural role. Further analysis is needed to verify the specific biocide tolerance mechanisms for each species.